An empirical relation to predict melting/burning losses in the ductile iron foundry. (2021) - Karinka, Shashikantha; Vijayan, Vijeesh; Bailkeri, Narasimha
Abstract: This paper is a case study of cast iron industry, which brings out the critical parameters that must be considered to reduce the burning/melting loss. The melting loss has been analyzed based on the different inputs to the induction furnace and the output as the molten metal. The various input parameters considered are boring material, briquettes, runners, steel, heel metal, pig iron, rejected/defect product etc. whereas the output is the weight of the molten metal. A detailed analysis show that the components such as boring material, scrap and pig iron in the charge increases the melting loss, while the additions such as runners, heel metal and coke reduce the melting losses. Based on the findings an empirical relation was derived to predict the burning losses during ductile iron melting which accordingly calculates the required amount of reduction agents such as coke to keep the melting loss within the limit.